Adsorption-Desorption Surface Bindings, Kinetics, and Mass Transfer Behavior of Thermally and Chemically Treated Great Millet Husk towards Cr(VI) Removal from Synthetic Wastewater - Anuj Kumar Prajapati; Pushkar Verma; Satyansh Singh; Monoj Kumar Mondal (Adsorption Science & Technology)
This study reports the efficacy of adsorbents synthesized by thermal (TT-GMH) and chemical (CT-GMH) modification of great millet husk (GMH) for the treatment of synthetic wastewater containing Cr(VI). The chemical modification of raw GMH was done by concentrated H2SO4 to increase the porosity and heterogeneity on the surface. The comparative investigations of physicochemical properties of synthesized adsorbents were examined by point of zero charge (pHpzc), BET surface area, SEM-EDX, FTIR, and XRD analyses. The results revealed that CT-GMH had around three times higher surface area and more porous structure as compared to TT-GMH. The adsorption experiments were executed in batch mode to examine the impact of parameters governing the adsorption process. For Cr(VI) solution of 25 mg/L, adsorbent dose of 4 g/L, temperature of 25°C, and shaking speed of 150 RPM, the maximum removal for TT-GMH was attained at pH 1 and contact time 150 min, while for CT-GMH, maximum removal was attained at pH 2 and contact time 120 min. The experimental results fitted to the rate kinetic equations showed that for both TT-GMH and CT-GMH, adsorbents followed the quasi-second-order kinetic model during the adsorption process. Further, results revealed that the adsorption process was endothermic and Sips isotherm model was followed for both TT-GMH and CT-GMH. Based on the Sips isotherm, maximum uptake capacity for TT-GMH and CT-GMH was noted to be 16 and 22.21 mg/g, respectively. Among the tested mass transfer models, liquid film diffusion model was followed during the adsorption process of both the adsorbents. The desorption study revealed that TT-GMH and CT-GMH give 69.45% and 74.48% removal, respectively, up to six cycles.